Effective Inclusion Program Suggestions From Around the World - David Aloyzy Zera (Networks: An Online Journal for Teacher Research, 2002)
Reflection, inquiry, and action are interrelated in teacher research because teachers act as thinkers, learners, and practitioners throughout their studies (Patterson & Shannon, 1993, p. 10). Some facets of action inquiry may be more intensely implemented than others (e.g., reflection over inquiry, inquiry over action, etc.), but the fact remains that at some point in the process, all facets are explored in some fashion. The purposes of these facets are to foster dialogue and open avenues of thought that may effect positive change in naturalistic settings. Rather than being outside the system, it is important for professionals who interact within the system to dialogue effectively and share their insights, data, and newfound information. There is a reciprocal relationship in that research guides practice, teachers implement the practice, and further research examines its efficacy. Without the dialogue, systems may not change, and advances in knowledge cannot take place.